Molecular mechanisms of transgenerational epigenetic inheritance - Fitz-James, Maximilian H; Cavalli, Giacomo (Nature reviews. Genetics, 2022)
Increasing evidence indicates that non-DNA sequence-based epigenetic information can be inherited across several generations in organisms ranging from yeast to plants to humans. This raises the possibility of heritable 'epimutations' contributing to heritable phenotypic variation and thus to evolution. Recent work has shed light on both the signals that underpin these epimutations, including DNA methylation, histone modifications and non-coding RNAs, and the mechanisms by which they are transmitted across generations at the molecular level. These mechanisms can vary greatly among species and have a more limited effect in mammals than in plants and other animal species. Nevertheless, common principles are emerging, with transmission occurring either via direct replicative mechanisms or indirect reconstruction of the signal in subsequent generations. As these processes become clearer we continue to improve our understanding of the distinctive features and relative contribution of DNA sequence and epigenetic variation to heritable differences in phenotype.